2008
DOI: 10.5713/ajas.2008.80201
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effectiveness of Methionine Hydroxy-analogue Calcium Salt in Relation to DL-Methionine in Broiler Chickens

Abstract: Two feeding trials were conducted to assess the relative bioavailability (RBV) of methionine hydroxy analogue calcium salt (MHA-Ca) in comparison to DL-methionine (DL-Met). Male Ross 308 (1-38 days) and Cobb 500 chickens (1-42 days) were used in studies 1 and 2, respectively. Experimental diets based on wheat and soybean meal or sorghum and soybean meal were fed during three phases. In both experiments graded levels of DL-Met and MHA-Ca were supplemented to Met+Cys deficient basal diets. Additionally, in exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
3
22
1
2
Order By: Relevance
“…To the best of our knowledge, there are no previous published data on the RBV of MHA-Ca and DL-Met to support N retention and performance in pigs. It has been recently reported that, on a product-toproduct basis, the RBV of MHA-Ca relative to DL-Met was 63% in broiler chickens (Elwert et al, 2008) and 66% in chicks fed Met-deficient basal diet (Dilger and Baker, 2008). These RBV values are slightly lower than the RVB value of 71% on a product-to-product basis observed in the current study.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…To the best of our knowledge, there are no previous published data on the RBV of MHA-Ca and DL-Met to support N retention and performance in pigs. It has been recently reported that, on a product-toproduct basis, the RBV of MHA-Ca relative to DL-Met was 63% in broiler chickens (Elwert et al, 2008) and 66% in chicks fed Met-deficient basal diet (Dilger and Baker, 2008). These RBV values are slightly lower than the RVB value of 71% on a product-to-product basis observed in the current study.…”
Section: Discussioncontrasting
confidence: 80%
“…In a recent study, Elwert et al (2008) reported that the mean RBV of MHA-Ca to DL-Met was 63% on a product-toproduct basis in broiler chickens. Likewise, Dilger and Baker (2008) reported that MHA-Ca was 65.6% as efficacious as DL-Met on a product-to-product basis in chicks.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…There have already been many discussions concerning the relative bioavailability of methionine from different sources, as well as a considerable number of experiments comparing various sources, mainly DL-HMBA and DLM, conducted in birds (Esteve-Garcia and Llaurado, 1997;Hoehler et al, 2005a;Elwert et al, 2008). Furthermore, the correct statistical design to evaluate the bioavailability of different sources of essential nutrients has been under debate (Littell et al, 1997;Kratzer and Littell, 2006;Piepho, 2006).…”
Section: Introductionmentioning
confidence: 99%